Inside Out & Back Again - Lai, Thanhha (New York : Harper, 2011)
Through a series of poems, a young girl chronicles the life-changing year of 1975, when she, her mother, and her brothers leave Vietnam and resettle in Alabama.
Ages 8-12.
Keywords: Vietnamese Americans -- Fiction; Immigration and emigration -- Fiction; Immigrants -- Fiction; Vietnam -- History -- 20th century; Alabama -- Fiction -- History -- 20th century